Tunisia : 2009 Article IV Consultation; Staff Report; and Public Information Notice. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that Tunisia has weathered the impact of the current crisis relatively well. Real GDP growth slowed down from an average of 4.6 percent in 2008 to 0.5 percent in the first quarter of 2009, reflecting mainly a fall in exports of manufactured goods to European Union countries. Executive Directors have commended the authorities for the good performance of the Tunisian economy in the context of the global crisis, owing to strong fundamentals resulting from sound policies implemented over the years.